1978
DOI: 10.1007/bf00233883
|View full text |Cite
|
Sign up to set email alerts
|

Organization of the sympathetic innervation in liver tissue from monkey and man

Abstract: The sympathetic innervation of the liver of monkey and man has been investigated in a combined fluorescence histochemical, chemical and electron microscopical study. By means of the Falck-Hillarp fluorescence method a dense network of monoamine-containing nerve fibers was visualized in liver tissue of monkey and man. The nerve fibers ran in close contact to both hepatocytes and blood vessels. Chemical quantitations showed high concentrations of noradrenaline in both human and monkey liver. Microspectrofluorome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
41
0

Year Published

1982
1982
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 18 publications
4
41
0
Order By: Relevance
“…The present electron microscopic study on the guinea pig liver for the first time gave the morphological data supporting the secretion of neurotransmitter substance from the vesiculate varicosities of the portal canal nerves. Thus, the present study has given electron microscope evidence that the blood vessels distributed in the portal canal may receive adrenergic control as claimed by NOBIN et al (1978). In their review on the hepatic innervation, MCCUSKEY et al (1979) described that nothing is known about hepatic sensory nerves.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…The present electron microscopic study on the guinea pig liver for the first time gave the morphological data supporting the secretion of neurotransmitter substance from the vesiculate varicosities of the portal canal nerves. Thus, the present study has given electron microscope evidence that the blood vessels distributed in the portal canal may receive adrenergic control as claimed by NOBIN et al (1978). In their review on the hepatic innervation, MCCUSKEY et al (1979) described that nothing is known about hepatic sensory nerves.…”
Section: Discussionsupporting
confidence: 67%
“…Since the light microscopic study on the Innervation of mammalian liver carried out by RIEGLE (1928) with the silver impregnation method, many investigations have been carried out to elucidate the nature of nerves supplying the liver with a variety of methods: not only electron microscopy but also histochemistry for cholinesterase, fluorescence method, autoradiography using 3H-noradrenalin, and chemical denervation of sympathetic nerves with 6-OH-dopamine (SUTHERLAND, 1964;UNGVARY and DONATH, 1969;ANUFRIEW et al, 1973;SATLER et al, 1974;SKAARING and BIERRING, 1976;FORSSMANN and ITO, 1977;UNO, 1977;REILLY et al, 1978;NOBIN et al, 1978;MCCUSKEY et al, 1979;SAWCHENKO and FRIEDMAN, 1979). YAMADA (1965), ITO and SHIBASAKI (1968) and TSUNEKI and ICHIHARA (1981) utilized transmission electron microscopy (TEM) to study the innervation of the liver in man, the monkey, mouse, several other mammals, birds and lower vertebrates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These branches travel through sinusoids to supply the lobules, where terminal branches surround perisinusoidal cells and hepatocytes. 39,40 Parasympathetic or cholinergic nerve fibers have been shown to innervate extrahepatic and intrahepatic branches of the HA, PV, and hepatic vein. Cholinergic innervation of hepatocytes and sinusoids is however sparse.…”
Section: Nerves In the Livermentioning
confidence: 99%
“…It thus appears that splanchnic nerve stimulation may trigger the influx of Ca2+ ions into liver cells, leading to activation of phosphorylase kinase and then phosphorylase. Electron microscopic studies ofthe hepatic innervation have revealed nerve terminals in direct contact with some of the hepatocytes; these terminals are commonly embedded in indentations in parenchymal cells and contain both clear and dense-cored vesicles (Yamada, 1965;Forssmann & Ito, 1977;Nobin, Baumgarten, Falck, Ingemansson, Moghimzadeh & Rosengren, 1978). These morphological observations, together with the fact that stimulation or depolarization of presynaptic nerves enhances Ca2+ influx in both presynaptic and post-synaptic elements in sympathetic ganglia (Robinson & Kabela, 1977;Blaustein, 1976) and in neuromuscular junctions (Miledi, Parker & Schalow, 1980), support this proposition.…”
Section: Discussionmentioning
confidence: 91%